The relationship between audit committee effectiveness and the level of corporate risk disclosure: the relevance of pre-and post-Mccg 2012 / Sarliza Saari … [et al.] - Saari, Sarliza; Mohd Suffian, Mohd Taufik; Abd Ghafar, Mohd Shatari; Mohamed Azhari, Muhammad Iqbal (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
This study examined the relationship between audit committee effectiveness and the level of corporate risk disclosure amongst Malaysian listed companies pre- and post-Malaysian Code of Corporate Governance 2012. Content analysis was employed. A total of 122 firm-year observations was examined in order to measure the extent of risk disclosure against audit committee effectiveness. The findings reveal only audit committee size and diligence are significant in explaining the variations in corporate risk disclosure for pre- and post-MCCG 2012. This indicates that audit committee size does matter in assisting the revelation of corporate risk disclosure. It also signifies that audit committees are responsible and discharge their duties accordingly with reference to the higher number of audit committee meetings. An unexpected result was also found in this study where an inverse relationship was detected between audit committee independence and corporate risk disclosure. The result is contrary to the requirement of MCCG 2012 that emphasizes the importance of an independent director under its Principle 3.5. Further, the result also shows that the audit committee effectiveness have increasing in the post-MCCG 2012 period compared to pre-MCCG 2012 in determining the extent of risk disclosure of the sampled firms.